Special needs of Muslim family tourists across the family life cycle: stakeholders’ perspectives - Osman, Fatin Norain; Hussin, Siti Rahayu; Raja Yusof, Raja Nerina; Hashim, Haslinda; Abdul Aziz, Yuhanis; Nezakati, Hossein (American-Eurasian Network for Scientific Information (AENSI) Publications, 2015)
The growing popularity of Islamic tourism has captured the interest of academics and practitioners all over the world. The extant literature have examined tourists’ motivations and destination choice from the tourists perspectives, however, little have been examined from the perspectives of those involved in providing services to the tourists. These service providers include government agencies in-charge of tourism sector, the destination operators such as theme parks, the lodging provider such as hotels and homestays, and the travel agents who deal closely with the tourists. This research offers the model of Family Life Cycle, as a theoretical framework to examine the travelling decisions made by family tourists at different stages in the family life cycle. The novelty of this paper is in defining the Muslim tourists. Here, Muslim tourists refer to tourists whose religion is Islam. i.e. tourists who are Muslims and came to Malaysia and local tourists who are Muslims who travel in Malaysia. This is in contrast to the Muslim tourists who is defined in existing literature as Muslims who go for pilgrimage and consume Islamic-related tourism products and services. The study takes a different approach by examining the perspectives of stakeholders instead of the tourists. The research aimed to ascertain the stakeholder’s perceptions about the travel decisions made by family tourists and the commonalities with these group of tourists (i.e., tourists’ decisions on destination choice, facilities/services required, and shared behavior). Using qualitative method, this study investigated the specific requirements of Muslim family needs while travelling. A series of focus groups with stakeholders and service providers in the tourism sector in Malaysia was conducted in 2014. Six groups of informants were interviewed based on their participation in the Islamic tourism in Malaysia. The findings indicated three major themes which are specific to Muslim tourists i.e. cultural-influence (religion), customer characteristic (stage in family life cycle) and destination services (family-friendly facilities). Factors such as family togetherness activities, family travel packages, family-friendly environment, wellness facilities for Muslim women; Muslim-friendly environment, etc. were among the factors repeatedly highlighted by the six different groups of informants with regards to the special needs of Muslim family tourists. The study concluded that there is a need to revisit family tourists’ behaviour as the Muslims tourists seemed to have specific requirements on their own. Specifically, the study recommended that a new tourist typology is to be developed for Muslim family tourists.